A new method of analysis of granulated hops - Litvynchuk (Vorontsova), Svitlana; Nosenko, Volodymyr; Meletyev, Anatoly; Hutsalo, Inna (My University, 2013)
The diffuse reflectance spectra of hops were investigated in order to create a rapid method of assessing the quality of granulated hops with simultaneous determination of key indicators (without the use of chemicals and prolonged dry). Researches have been conducted on the infrared analyzer "Infrapid-61" in the wavelength range 1,33-2,37 microns.
Keywords: hops; analysis; moisture; α-acids; infrared analyzer; хміль; аналіз; вологість; α-кислоти; інфрачервоний аналізатор; кафедра фізики та професійної безпеки